The Socio-humanistic Рotential of Volunteering in Adaptive Sports - Irina Kogut (Lesya Ukrainka Volyn National University, 2016)
Nowadays, it is hard to imagine the organization and carrying out of the competitions without an active participation of volunteers. However, volunteering in adaptive sport is aimed not only at resolving of a number of organizational issues for successful sporting events, but it also has an extremely powerful socio-humanistic potential. Objectives of the work - 1. To find out the distinctive features of volunteering areas in adaptive sports. 2. To characterize the volunteer programs of the Special Olympics. 3. To determine the socio-humanistic potential of the volunteer program «United sport». 4. To analyze the factors that affect the social integration of people with disabilities. Research methods - analysis and generalization of the literature, information resources of the Internet, program and regulation sources; comparative method; abstraction, logical-theoretical analysis, content analysis. The results of the work. The problem of discrimination exists worldwide in various forms. Today a current topic is the adoption of measures to eliminate the problem of discrimination of people with disabilities. The possibility of full social integration of these people remains extremely relevant. The definition of the essence of social integration is contained in several international documents. However, the problem of implementing these provisions in practice is realised at a low level. Conclusions. The main directions of volunteers' work in the Paralympic and Deaflympic sports are similar to the Olympic and mainly aimed at the successful organization and conduction of the competitions. However, the functioning of the Special Olympics movement is built entirely on the activities of the various volunteer programs aimed at solving not only organizational issues but they also provide the training and competitive process, the implementation of educational, recreational, informational, social and humanistic mission. Volunteer program «United sport» creates the conditions for the solution of problems on the way of social integration. It is gradually changing the negative attitude and actions to positive perception of people with disabilities.